2008
DOI: 10.1186/1471-2474-9-112
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders among Nigerian Physiotherapists

Abstract: Background: Physiotherapists are known to be prone to Work-related musculoskeletal disorders (WRMDs) but its prevalence among physiotherapists in Nigeria has not been reported. This study investigated the prevalence and work factors of WRMDs among physiotherapists in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
216
9
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(271 citation statements)
references
References 19 publications
34
216
9
12
Order By: Relevance
“…In the present study, WRMD prevalence was 88% in male physical therapists and 97% in female physical therapists, similar to the rates reported by Adegoke et al 15) of 86% in male physical therapists and 100% in female physical therapists. The higher rate for females was because women are physically weaker than men increasing their risk of injury when lifting and transferring patients.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the present study, WRMD prevalence was 88% in male physical therapists and 97% in female physical therapists, similar to the rates reported by Adegoke et al 15) of 86% in male physical therapists and 100% in female physical therapists. The higher rate for females was because women are physically weaker than men increasing their risk of injury when lifting and transferring patients.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Campo et al 14) observed that WRMD prevalence was higher in older physical therapists than in younger physical therapists. In contrast, most previous studies have reported that therapists experience symptoms before they reach 30 years of age, and the incidence rate within 5 years of graduation is high 5,9,11,12,15) . The suggested reason is that new physical therapists lack professional experience, knowledge, and techniques, and that they are rotationally dispatched to different places, thereby running a higher risk of injury 1,16) .…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations